IMPLEMENTASI PLATFORM ELECTRONIC COMMERCE SEBAGAI MEDIA PEMASARAN HASIL PERTANIAN DI DESA - Yansahrita, Yansahrita; Riswari, Andini Tia; Fauzi, Fauzi (STMIK Pringsewu, 2024)
Pringsewu Regency has great potential in the agricultural sector in Lampung Province. Agriculture is the potential for using the internet in business activities as a medium for carrying out trade transactions. Ease of access to electronic communication tools is one of the reasons for the increasing growth in the use of e-commerce in various countries, including Indonesia. Farmers can market agricultural products directly to consumers through marketplace-based e-Commerce applications, so that the marketing distribution chain can be cut and have an impact on profits for farmers. Farmers' knowledge about the use of social media and e-commerce is lacking, the application of technology in the form of social media and e-commerce is needed to increase the marketing reach of agricultural and livestock products, and further and sustainable development so that the community does not rely on producing and selling agricultural products in the form of raw. This research aims to increase market reach for agricultural products which requires technology that can reach wider marketing reach. The application of technology offered is the use of social media and e-commerce, as well as evaluating the effectiveness of marketing using social media and e-commerce